2017
DOI: 10.1136/bjsports-2017-097962
|View full text |Cite
|
Sign up to set email alerts
|

Sport, sex and age increase risk of illness at the Rio 2016 Summer Paralympic Games: a prospective cohort study of 51 198 athlete days

Abstract: Objective To describe the epidemiology of illness at the Rio 2016 Summer Paralympic Games. Methods A total of 3657 athletes from 78 countries, representing 83.5% of all athletes at the Games, were monitored on the web-based injury and illness surveillance system (WEB-IISS) over 51 198 athlete days during the Rio 2016 Summer Paralympic Games. Illness data were obtained daily from teams with their own medical support through the WEB-IISS electronic data capturing systems. results The total number of illnesses wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 17 publications
17
78
0
Order By: Relevance
“…The respiratory system was the most affected by illness, which is in agreement with results from both the Paralympic Games and Olympic Games . Previous studies have indicated that especially athletes with SCI are more susceptible to infections . However, in the present study, athletes with SCI did not have significantly more illnesses when compared to other impairment groups.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The respiratory system was the most affected by illness, which is in agreement with results from both the Paralympic Games and Olympic Games . Previous studies have indicated that especially athletes with SCI are more susceptible to infections . However, in the present study, athletes with SCI did not have significantly more illnesses when compared to other impairment groups.…”
Section: Discussionsupporting
confidence: 91%
“…Female athletes had significantly more existing illnesses, both in the present study and in the study from the 2016 Summer Paralympic Games. Thus, a focus on this athlete group with regard to illness prevention is recommended …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations